2020
DOI: 10.1108/jkm-05-2020-0332
|View full text |Cite
|
Sign up to set email alerts
|

Systematization of absorptive capacity microprocesses for knowledge identification in project management

Abstract: Purpose This study aims to systematize the acquisition phase of absorptive capacity microprocesses that contribute to project management (PM) knowledge identification. Design/methodology/approach An exploratory and descriptive qualitative research was adopted. The first stage consisted of building the conceptual framework based on four systematic-literature-reviews. The data collection process in the second phase involved in-depth interviews, which are adequate to understand the interviewee’s reality. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
8
0
1
Order By: Relevance
“…Despite all these variables that might seem unrelated, there is one holistic concept that can frame them together. In fact, knowledge management, which is a key concept of ACAP theory (Moraes et al , 2020), is also the leitmotif of the investigated concepts, i.e. ACAP, circular economy, life cycle approach, performance and reputation.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Despite all these variables that might seem unrelated, there is one holistic concept that can frame them together. In fact, knowledge management, which is a key concept of ACAP theory (Moraes et al , 2020), is also the leitmotif of the investigated concepts, i.e. ACAP, circular economy, life cycle approach, performance and reputation.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…'s (2018) study, which found no direct relationship between knowledge sharing practices and PP but postulated that these practices affect improvement in a project's AC. Moraes et al. (2020) also highlight that lessons learned from previous projects are the primary knowledge transfer mechanism.…”
Section: Resultsmentioning
confidence: 94%
“…These findings are consistent with Ali et al's (2018) study, which found no direct relationship between knowledge sharing practices and PP but postulated that these practices affect improvement in a project's AC. Moraes et al (2020) also highlight that lessons learned from previous projects are the primary knowledge transfer mechanism. And Hughes et al (2014) complement that network relationships are crucial to improve the ability to assimilate and exploit knowledge.…”
Section: Ac Effects On Pp In the Construction Industrymentioning
confidence: 94%
“…PLM system combined with cognitive evaluation theory, equity theory, social comparison theory, product research and development team members performance evaluation model was constructed to researchers the day-to-day work of the data into big data analysis, combining with the implementation of enterprise itself has the information function, achieve the goal of enterprise management digital integration, will manage the accuracy from the project direction to personnel management direction, And improve the responsibilities of administrative leadership, improve the efficiency of project management [48][49][50][51][52].…”
Section: Methodsmentioning
confidence: 99%